Seqüenciamento de peptídeos usando espectrometria de massas: um guia prático - Cantú, Marcelo Delmar; Carrilho, Emanuel; Wulff, Nelson Arno; Palma, Mario Sergio [UNESP] (Sociedade Brasileira de Química, 2008)
This paper introduces the basics of peptide mass spectra interpretation applied to proteomics and is directed to chemists, biochemists and biologists. The manuscript presents a well detailed protocol aiming to serve as a first choice guide for understanding peptide sequencing. The tutorial was elaborated based on both a thorough bibliographic revision and the author's experience. In order to prove the applicability of the proposed guide, spectra obtained on different instruments have been successfully interpreted by applying the presented rational.
Peptide sequencing using mass spectrometry: a practical guide
Keywords: proteomic analysis; mass spectrometry; peptide sequencing